Dental care of the pregnant patient: an update of guidelines and recommendations - Hyder, Tahira; Khan, Saifullah; Moosa, Zuhair Haroon (Journal of the Pakistan Medical Association, 2023)
Pregnancy is a dynamic state marked by several physiological changes. Oral healthcare in pregnancy is often avoided and misunderstood, with healthcare professionals struggling to interpret the safety and appropriateness of dental treatment during this period. Despite international guidelines and consensus reports indicating that preventive and restorative dental treatment are safe and essential, there is still a widespread belief among healthcare professionals and general population in Pakistan that dental treatment during pregnancy may pose damage to the foetus. Over the past three decades, as human knowledge of the biology behind periodontal diseases broadened, its systemic impact upon various physiological states is better understood and management protocols are accordingly formulated. Lack of knowledge among dentists regarding the timing of routine dental treatment, avoidance of certain medications and poor understanding of the clinical changes in the periodontium of the pregnant patient needs to be addressed so that timely treatment is provided. —Continue